The genomes uncoupled Mutants Are More Sensitive to Norflurazon Than Wild Type. Issue 3 (12th September 2018) - Song, Lijuan; Chen, Zefan; Larkin, Robert M.
Abstract : The increased sensitivity of the genomes uncoupled mutants to norflurazon indicates that they are probably deficient in plastid-to-nucleus signaling and are unequivocally not resistant to norflurazon.